The Contribution of Gut Barrier Changes to Multiple Sclerosis Pathophysiology - Buscarinu, Maria Chiara; Fornasiero, Arianna; Romano, Silvia; Ferraldeschi, Michela; Mechelli, Rosella; Reniè, Roberta; Morena, Emanuele; Romano, Carmela; Pellicciari, Giulia; Landi, Anna Chiara; Salvetti, Marco; Ristori, Giovanni (Frontiers in Immunology, 2019)
The gut barrier consists of several components, including the mucus layer, made of mucins and anti-bacterial molecule, the epithelial cells, connected by tight junction proteins, and a mixed population of cells involved in the interplay with microbes, such as M cells, elongations of “antigen presenting cells” dwelling the lamina propria, intraepithelial lymphocytes and Paneth cells secreting anti-bacterial peptides. Recently, the influence of intestinal permeability (IP) changes on organs far from gut has been investigated, and IP changes in multiple sclerosis (MS) have been described. A related topic is the microbiota dysfunction that underpins the development of neuroinflammation in animal models and human diseases, including MS. It becomes now of interest to better understand the mechanisms through which IP changes contribute to pathophysiology of neuroinflammation. The following aspects seem of relevance: studies on other biomarker of IP alterations; the relationship with known risk factor for MS development, such as vitamin D deficiency; the link between blood brain barrier and gut barrier breakdown; the effects of IP increase on microbial translocation and microglial activation; the parallel patterns of IP and neuroimmune changes in MS and neuropsychiatric disorders, that afflict a sizable proportion of patients with MS. The therapeutic implications of IP changes will be also discussed, considering the impact of MS-modifying therapies on gut barrier, as well as potential approaches to enhance or protect IP homeostasis